Disinhibition of Cathepsin C Caused by Cystatin F Deficiency Aggravates the Demyelination in a Cuprizone Model - Liang, Junjie; Li, Ning; Zhang, Yanli; Hou, Changyi; Yang, Xiaohan; Shimizu, Takahiro; Wang, Xiaoyu; Ikenaka, Kazuhiro; Fan, Kai; Ma, Jianmei (Frontiers in Molecular Neuroscience, 2016)
Although the precise mechanism underlying initial lesion development in multiple sclerosis (MS) remains unclear, CNS inflammation has long been associated with demyelination and axonal degeneration. The activation of microglia/macrophages, which serve as innate immune cells in the CNS, is the first reaction to even minor pathologic changes in the CNS and is considered an initial pathogenic event in MS. Microglial activation accompanies a variety of gene expressions, including cystatin F (Cys F), which belongs to the cystatin superfamily and is one of the cathepsin inhibitors. In our previous study we showed that Cys F has a unique expression pattern in microglia/macrophages in the demyelination process. Specifically, the timing of Cys F induction correlated with ongoing demyelination, and the sites of Cys F expression overlapped with areas of remyelination. Cys F induction ceased in chronic demyelination when remyelination capacity was lost, suggesting that Cys F expressed by microglia/macrophages may play an important role in demyelination and/or remyelination. The functional role of Cys F in demyelinating disease of the CNS, however, is unclear. Cys F gene knock out mice were used in the current study to clarify the functional role of Cys F in the demyelination process in a cuprizone-induced demyelination animal model. We demonstrated that absence of the Cys F gene and the resulting disinhibition of cathepsin C (Cat C) aggravates the demyelination, and this finding may be related to the increased expression of the glia-derived chemokine, CXCL2, which may attract inflammatory cells to sites of myelin sheath damage. This effect was reversed by knock down of the Cat C gene. The findings gain further insight to function of Cat C in pathophysiology of MS, which may have implications for therapeutics for the prevention of neuroinflammation-involved neurological disorders in the future.